(untitled) (The Journal of Psychology and Sociology, 2023)
The article presents the data of an empirical study aimed at identifying gender and age differences and features of current functional state of an individual and opposition to changes in a condition of crisis. The obtained research results can serve as a theoretical foundation in a positive and crisis psychology in the study of the possibilities of psychological self-development of a person and it can be used by practi-cal psychologists in working with people during a crisis to improve personal and social well-being. In the process of research the following methods were translated and adopted into Kazakh: “Personal readi-ness to changes» by A. Rolnik, S.Heather, M.Gold, С.Hall and “, «Ermüdung-Monotonie-Sättigung-Streß” (Fatigue – monotony – satiety – stress) by H-E.Plath, P.Richter. Alpha – Kronbach methods “Personal readiness to changes” – 0.935 “Ermüdung-Monotonie-Sättigung-Streß” (Fatigue – monotony – satiety – stress) – 0.933. The psychometric indicators of the techniques are quite high. The results of the study revealed the differences in current functional state and opposition to changes between people of differ-ent ages and genders. Key words: functional state, opposition to changes, crisis, pandemic.